INCREASING STUDENT’S RESEARCH WRITING BY APPLYING RESEARCH BASED INSTRUCTION - Moon Hidayati Otoluwa; Ivan Rismi Polontalo (Universitas Negeri Padang, 2013)
Recently, a promising model of teaching and learning is an engagement of students and teacher into theory and practice of learning. Doing a more theoretical and discussion models of learning are good to make students understand a topic, but in contrast they are not good in practice. A combination of less theoretical and more practical model of learning, called research-based learning, which allows students to learn things in practice and to train them to analyze and criticize situations deeply, was developed to help students learning various topics based on researches and practice their critical analysis. This study focused on the investigation to see students experience in learning writing skills through the application of research based instruction and see how the model of learning givesthem chance to finish their Skripsi (a research project conducted as a prerequisite of a bachelor degree). Subjects in this study were 60 EFL students enrolled in the Seminar on Language class at English Department of the Faculty of Letters and Cultures in Universitas Negeri Gorontalo. By applying an action research method, students showed significant changes in critical learning performance. The investigation included 2 systematic cycles – Planning, Action, Observation, and Reflection. The results of the study showed that the application of RBI was helpful for the students to help them finishing their final project (the Skripsi), particularly for students of English Department. Most students perceived positively toward the Research based Instruction in the learning process.